2007
DOI: 10.1088/1741-2560/4/2/006
|View full text |Cite
|
Sign up to set email alerts
|

Conditional firing probabilities in cultured neuronal networks: a stable underlying structure in widely varying spontaneous activity patterns

Abstract: To properly observe induced connectivity changes after training sessions, one needs a network model that describes individual relationships in sufficient detail to enable observation of induced changes and yet reveals some kind of stability in these relationships. We analyzed spontaneous firing activity in dissociated rat cortical networks cultured on multi-electrode arrays by means of the conditional firing probability. For all pairs (i, j) of the 60 electrodes, we calculated conditional firing probability (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
98
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(110 citation statements)
references
References 33 publications
2
98
0
Order By: Relevance
“…Intracellular experiments showed that presynaptic spikes that precede postsynaptic firing by up to ∼30 ms lead to long-term potentiation of the connecting synapse (Bi and Poo 1998;Zhang et al 1998;Song et al 2000). Functional connections between neurons that have a latency in this range also tend to become strengthened in spontaneously active cultured cortical networks (le Feber et al 2007(le Feber et al , 2009). This adds justification to our assumption that neurons with ongoing activity have relatively strong synapses (intense neurons).…”
Section: Simulated Datamentioning
confidence: 99%
“…Intracellular experiments showed that presynaptic spikes that precede postsynaptic firing by up to ∼30 ms lead to long-term potentiation of the connecting synapse (Bi and Poo 1998;Zhang et al 1998;Song et al 2000). Functional connections between neurons that have a latency in this range also tend to become strengthened in spontaneously active cultured cortical networks (le Feber et al 2007(le Feber et al , 2009). This adds justification to our assumption that neurons with ongoing activity have relatively strong synapses (intense neurons).…”
Section: Simulated Datamentioning
confidence: 99%
“…In particular, during the second week in vitro they become wider and higher in firing rate. The third week is usually characterized by reduction and stabilization of NB firing rate and NB width (Van Pelt et al 2004a;Wagenaar et al 2006;Le Feber et al 2007;Stegenga et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…We used the term 'connection delay' to denote the time delay corresponding to the maximum of cross-correlation function which was regarded as connection strength. If connection delay was longer than 3 ms (Figure 2), the pair of electrodes was treated as synaptically connected [17]. Connectivity map characterized by connection strength and connection delay was constructed for each 20-or 60-minutes raster.…”
Section: Methodsmentioning
confidence: 99%
“…Functional connectivity was estimated by crosscorrelation analysis of spiking patterns of spontaneous network activity recorded through different microelectrodes (by analogy with [17]). The paper by le Feber [12] demonstrates that the integral indicator of neuronal network connectivity reorganization (Euclidean space between connectivity strength matrices for all pairs of recording electrodes before and after stimulation) changes after electrical stimulation.…”
Section: Connectivity Reorganization In the Networkmentioning
confidence: 99%
See 1 more Smart Citation